God as Father: The maleness of God - Williams, D. T. (Koers, 1990)
It is fashionable today to try to avoid sexist language in theology, despite the Bible’s consistent use of the masculine pronoun when referring to God. Although such an attempt has largely been engendered by modem culture, the maleness of God is not simply a hangover from a patriarchal society, but reflects a fundamental maleness in God’s dealing with man. It emphasises the idea of redemption by grace alone over against creation, and such aspects as the adoption of Christians as sons. The maleness of Christ likewise has not simply been cultural, but is significant theologically. This is not to deny any femininity in God, but to assert that male features predominate. Such an idea does not reduce the status of women, but rather an emphasis on redemption raises it. Raising the status of women in society would in fact reduce the pressure to demasculinize God.